2004
DOI: 10.1111/j.1096-0031.2003.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Myth of the molecule: DNA barcodes for species cannot replace morphology for identification and classification

Abstract: So-called DNA barcodes have recently been proposed to answer the problem of specimen identification and to quantify global biodiversity. We show that this proposition is wanting in terms of rationale, methodology and interpretation of results. In addition to falling short of all its stated goals, the method abandons the benefits of morphological studies in favor of a limited molecular identification system that would ultimately impede our understanding of biodiversity. Ó The Willi Hennig Society 2004.''If the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
341
0
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(364 citation statements)
references
References 27 publications
8
341
0
11
Order By: Relevance
“…Some studies, including extensive analyses of GenBank data, have indicated that even closely related species ordinarily show marked mitochondrial divergence (10,12). However, others suggest that mtDNA markers will often encounter problems in species resolution (28)(29)(30). For example, a review of case studies (31) concluded that nearly one-fourth of all animal species fail the test of mitochondrial monophyly.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, including extensive analyses of GenBank data, have indicated that even closely related species ordinarily show marked mitochondrial divergence (10,12). However, others suggest that mtDNA markers will often encounter problems in species resolution (28)(29)(30). For example, a review of case studies (31) concluded that nearly one-fourth of all animal species fail the test of mitochondrial monophyly.…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson et al (2004) show that phylogenetic analyses will outperform phenetic analyses in correctly identifying sequences. Will & Rubinoff (2004) also highlight the phenetic analyses of Hebert et al (2003a) as a weakness, and thus we incorporated both cladistic/phylogenetic analyses (maximum parsimony, MP) and phenetic/distance analyses (minimum evolution, ME; multi-dimensional scaling, MDS).…”
Section: Methodsmentioning
confidence: 99%
“…They argue that 'molecular taxonomy' can use 'DNA barcodes' to identify and classify nearly all animal life. Others have countered that this is a 'caricature of real taxonomy' (Lipscomb et al 2003), arguing that morphology must continue to play the central role (Dunn 2003;Will & Rubinoff 2004). They point out that assigning species boundaries with molecular data is no easier than with morphology (Will & Rubinoff 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification using DNA barcoding does not work if the DNA barcode sequences for the organism of interest do not exist in a public database like GenBank (Will & Rubinoff, 2004). Moreover, if the DNA barcode sequences of the organism of interest do not match the sequences existed in the public database, there will be 2 possibilities.…”
Section: Resultsmentioning
confidence: 99%